2012
DOI: 10.1111/j.1365-3113.2012.00617.x
|View full text |Cite
|
Sign up to set email alerts
|

Divergence estimates and early evolutionary history of Figitidae (Hymenoptera: Cynipoidea)

Abstract: We examine the phylogenetic relationships of Figitidae and discuss host use within this group in light of our own and previously published divergence time data. Our results suggest Figitidae, as currently defined, is not monophyletic. Furthermore, Mikeiinae and Pycnostigminae are sister‐groups, nested adjacent to Thrasorinae, Plectocynipinae and Euceroptrinae. The recovery of Pycnostigminae as sister‐group to Mikeiinae suggests two major patterns of evolution: (i) early Figitidae lineages demonstrate a Gondawa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 131 publications
5
49
0
Order By: Relevance
“…Images of T. japonicus collected in Beltsville, MD, are presented in Figures 1-5. To confirm morphological identifications, genomic DNA was extracted from the legs of 4 females, and one whole female specimen, using techniques summarized in Buffington et al (2012). The 'barcode' region of cytochrome oxidase I (COI) and the internal transcribed spacer region 2 (ITS2) regions were amplified and sequenced in the Scheffer Laboratory (USDA/ARS, Systematic Entomology Laboratory) and compared with sequences obtained from populations of previously identified Asian Trissolcus from Asian field surveys (Bon et al, unpublished).…”
Section: Species Identificationmentioning
confidence: 99%
“…Images of T. japonicus collected in Beltsville, MD, are presented in Figures 1-5. To confirm morphological identifications, genomic DNA was extracted from the legs of 4 females, and one whole female specimen, using techniques summarized in Buffington et al (2012). The 'barcode' region of cytochrome oxidase I (COI) and the internal transcribed spacer region 2 (ITS2) regions were amplified and sequenced in the Scheffer Laboratory (USDA/ARS, Systematic Entomology Laboratory) and compared with sequences obtained from populations of previously identified Asian Trissolcus from Asian field surveys (Bon et al, unpublished).…”
Section: Species Identificationmentioning
confidence: 99%
“…A preliminary analysis of the phylogeny of Figitidae demonstrated that the family was monophyletic (Ronquist 1999). Subsequent analyses, employing more thorough taxon and character sampling, found the family monophyletic (Buffington et al 2007) and paraphyletic (Buffington et al 2012), the latter study having recovered Cynipidae as sister-group to the figitid subfamilies Thrasorinae + (Pycnostigminae + Mikeiinae). Further phylogenetic interpretation of cynipoids is beyond the scope of this study, however, it should be pointed out that cynipids are very rare in the Afrotropical region, and the gall-associated figitid subfamilies Thrasorinae, Parnipinae, Mikeiinae and Plectocynipinae have not been recorded to date.…”
Section: Introductionmentioning
confidence: 95%
“…Afrotropical figitids are primarily endoparasitoids of Muscomorpha Diptera, attacking the early instar stages of their hosts and emerging from the host puparium (Buffington et al 2012). The two exceptions to this pattern are the Anacharitinae and Charipinae, of which the former are Chrysopidae parasitoids (Neuroptera), and the latter are hyperparasitoids of braconids and chalcidoids in plant lice (Sternorrhyncha) (Buffington et al 2012). Hosts are unknown for the Emargininae and Pycnostigminae, as well as numerous species of Eucoilinae.…”
Section: Figitidaementioning
confidence: 99%
See 2 more Smart Citations